(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
Camara Nusantara ship was provided for livestock transportation especially cattle, to help increasing efficiency and decrease weight losses in the supply chain process. There were, however, such poor cattle performance was still found on the arrival port, which was claimed as related to the poor management and less competence of working personnel on board, one of those was kleder. This study was aimed at analyzing the strategy for increasing Human Resource competency in the Camara Nusantara Livestock Ship. Method used in this study was observations on target location, documentation, literature review, and depth interviews with target respondents in the respective locations, qualitative analysis approach was applied for data analysis. Analytical Hierarchy Process (AHP) with five levels were used to analyze data obtained from the study. The results indicate that the main strategies for increasing the competency of human resource in the Camara Nusantara Livestock Ship was started with development of competency standardization with a weight of 0.361. Development of competency standards for kleder is required to provide a guidelines for improving kleder’s skills and knowledge in managing and handling livestock at Camara Nusantara Livestock Ship. It can be concluded that to optimize kleder competency who are working at Camara Nusantara Cattle Ship may help to maintain cattle performance during the sea toll transportation. Therefore, developing a national job competency standard, so called SKKNI (Standar Kompetensi Kerja Nasional Indonesia) is needed as guidance to formulate relevant training programs for human resource development.